2008
DOI: 10.1021/ja803230a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Nonstatistical Dynamics in the Wolff Rearrangement of a Carbene

Abstract: Two 13C-labeled isomers of the formal Diels−Alder adduct of acetylmethyloxirene to tetramethyl 1,2,4,5-benzenetetracarboxylate have been synthesized. Flash vacuum thermolysis of these adducts leads to various isotopic isomers of acetylmethylketene, the ratios of which have been determined by NMR. The surprising finding that the principal product comes from methylpyruvoyl carbene rather than its more stable isomer diacetylcarbene is explained by MPWB1K density functional calculations, which show that the reacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Such nonstatistical reaction dynamics have been reviewed in detail 7b,c. Molecular dynamics studies by Reyes and Carpenter, and Hase and co‐workers, as well as others have demonstrated the critical role of nonstatistical effects in reactions involving singlet biradicals,7a, 8 radical cations,9 and carbenes 10. Singleton and co‐workers have described nonstatistical pathways in alkene hydroborations,11 Diels–Alder reactions,12 and enyne–allene cyclizations 13.…”
Section: Methodsmentioning
confidence: 99%
“…Such nonstatistical reaction dynamics have been reviewed in detail 7b,c. Molecular dynamics studies by Reyes and Carpenter, and Hase and co‐workers, as well as others have demonstrated the critical role of nonstatistical effects in reactions involving singlet biradicals,7a, 8 radical cations,9 and carbenes 10. Singleton and co‐workers have described nonstatistical pathways in alkene hydroborations,11 Diels–Alder reactions,12 and enyne–allene cyclizations 13.…”
Section: Methodsmentioning
confidence: 99%
“…Although another way to calculate rates is Table 1 The thermodynamic parameters calculated by BPW91 method with 6-31G** basis set, energies of frontier molecular orbitals and global reactivity descriptors of 2-ABT, 2-IBT and 2-ABTH + structures. molecular dynamics, it has been shown that reacting molecules sometimes move on to a plateau region or a bifurcated region of the surface and then head toward products in directions determined by their internal motions [44]. Also, rigorous calculations of rate constants needs to utilize a specialized program based on RRKM (Rice-Ramsperger-Kassel-Marcus) theory [45,46].…”
Section: Molecular Structure and Quantum Chemical Investigationsmentioning
confidence: 99%
“…114 The paper reads like a detective story, chronicling hypotheses, tests, wrong steps, the fortuitous guidance offered by a referee, corrections, and a final summary. 114 The paper reads like a detective story, chronicling hypotheses, tests, wrong steps, the fortuitous guidance offered by a referee, corrections, and a final summary.…”
Section: A Look At the Wolff Rearrangementmentioning
confidence: 99%
“…Carpenter 114 was intrigued by the possibility of dynamical effects in carbene chemistry. He chose to explore the Wolff rearrangement taking 100 into 101.…”
Section: A Look At the Wolff Rearrangementmentioning
confidence: 99%